STRATEGI KOMUNIKASI BADAN PEMBERDAYAAN PEREMPUAN, MASYARAKAT DAN KELUARGA BERENCANA DALAM MENINGKATKAN PENGGUNA VASEKTOMI DI KOTA PEKANBARU - Nining Anggraini; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Since 1969, the Government has been doing the emphasis towards the rate of population by means of regulating births, maturation of marrying age, increasing the resilience of families and family welfare program called Family Planning. Based on the achievement of active participants on the Family Planning program in December 2015, men participation only 5.42% of the number of active participants, with details that the amount of participants used MOP contraceptive method are 0.21% and condom method are 5.21%. Based on the data show that Family Planning participants of the men still minor. The purpose of this research is to know the strategies of the introduction of the targets, the selection of media, the purpose of the message and the role of the Communicator which used by The Women, Community And Family Planning Board of Pekanbaru to increase the vasectomy’s users in Pekanbaru city.This research used qualitative methods through the collected data obtained in field through observation, interview and documentation. The informant of this research consists of 7 persons. They are consist of one chair division of The Women, Community And Family Planning Board of Pekanbaru. And four persons are unit work actors, one person from field extension officers and other person from vasectomy’s users which selected through the technique of purposive sampling. To analyze the results of this research writer used the interactive model data analysis techniques, whereas the technique examination validity of the data through the extension of participation and triangulation.The result of the research show that communication strategy of The Women, Community And Family Planning Board in terms of the promotion of target that the whole people especially men in Pekanbaru. The selection of media divided into mass media and direct media. The mass media such as newspapers and radio. Then, direct media through media outreach-extension in the field and opening stand of information. The contents of the message that conveyed by the The Women, Community And Family Planning Board of Pekanbaru are persuasive, educative and informative messages. After contents of the message submitted, the vasectomy’s user will see communicator role in communication that includes attraction of resources and credibility of source.Keywords: Communication strategy, Vasectomy